THE SPRAWL OF URBAN COASTAL SPACE AND ITS RELATIONSHIP TO THE POLLUTION OF WATER RESOURCES ALONG THE COCO COAST, NICOYA PENINSULA, COSTA RICA - Orias-Arguedas, Lidia (Revista Geográfica de América Central., 2013)
This research was conducted in the El Coco coastal urban area belonging to the Sardinal District of the Canton of Carrillo in the Nicoya Peninsula, which shows rapid growth in tourism-related activ -ity and the subsequent increase in water resource consumption. This situation leads to a high vul -nerability of contamination to the El Coco aquifer. Wells potentially vulnerable to contamination were identified and characterized and correlated with the map of vulnerability to contamination. Likewise, areas of Perimeter Protection Wells were identified along with capture or well-loading zones. Open interviews were used as primary sources. Photo interpretationand remote sensingtech -niques were employed along with Geographic Information Systems.